DISTINCT BY GOD’S WORD: DIVERSITY AND THE THEOLOGY OF RELIGIONS - P. Sheridan, Daniel (Journal of Dharma, 1988)
On October 28, 1965, the bishops of the Roman Catholic Communion, gathered at St. Peter’s for the Second Vatican Council, promulgatedNostrs Aetste, On the Relationship of the Church to Non-Christian Religions. This document had an interesting but up and down history at the Council. That Council, which had been called to renew the Church, was naturally led to promoting Ecumenism among Christian ecclesial bodies. Promoting Ecumenism among Christians led to the question of the relationship of the Church of the New Covenant to the abiding reality of the people of Abraham’s stock, the sons and daughters of the Mosaic Covenant. A Statement on judaism had originally been appended to the Decree on Ecumenism. Once separated from the treatment of Christian Ecumenism, the Council’s Statement on judaism was expanded to include the other non-Christian religions. Thus it was only as an afterthought to the Church’s relationship to judaism that the Council gave consideration in a formal way to the rest of God’s People, those neither jews nor members of the visible Church in any of its forms. This extremely cautious afterthought is nevertheless a startling revival of the very old tradition of the Christian faith as the complete expression of truths only incompletely expressed in the religions, a tradition which viewed revelation in quantitative terms as a progress toward fullness